Research advances in serum chitinase-3-like protein 1 in liver fibrosis - Hu, Xingwei; Liu, Wenhan; Liu, Jianhua; Wang, Bojian; Qin, Xiaosong (Frontiers in Medicine, 2024)
While liver fibrosis remains a serious chronic progressive liver disease, short-term liver fibrosis is reversible. If factors causing damage persist, liver fibrosis may develop into cirrhosis and liver cancer. a serious, progressive, chronic liver disease, and factors causing damage persist, liver fibrosis may develop into cirrhosis and liver cancer.However, short-term liver fibrosis is reversible.Therefore, an early diagnosis of liver fibrosis in the reversible transition phase is important in the for effective treatment of liver diseases. Chitinase-3-like protein 1 (CHI3L1), an inflammatory response factor that participates in various biological processes and is enriched in is abundant in liver tissue, may be a good biomarker holds promise as a potential biomarker for liver diseases. We Here, we aimed to review research developments concerning regarding serum CHI3L1 in relation to the pathophysiology and diagnosis of liver fibrosis of various etiologies to provide , providing a reference for the diagnosis, treatment, and prognosis of liver diseases.